Energy-saving glasses based on sodium tungsten bronze-like (Na5W14O44) functional units: Facile synthesis, NIR-shielding performance, and formation mechanism. Issue 15 (1st August 2022) - Yang, Guang; Yang, Chuanfan; Xia, Fang; Hu, Daming; Brugger, Joël; Etschmann, Barbara E.; Hamilton, Jessica; Chen, Hongfei; Gao, Yanfeng
Abstract: Near-infrared (NIR)-shielding glasses for energy-saving window applications were prepared by forming sodium tungsten bronze-like (Na5 W14 O44 ) functional units in the 29SiO2 –43B2 O3 –28NaF glass matrix. The glasses were synthesized by a facile melt-quenching process where 4–8 mol.% H2 WO4 was added as the W source. The optimal glass was produced using 6 mol.% H2 WO4, which had a low NIR transmission of 15.4% and a high visible light transmission of 59.8%. The possible mechanism for the formation of Na5 W14 O44 in glasses were discussed based on XRD, Raman, XPS, XANES and EXAFS characterization of the glass samples, the glass samples after further crystallization, and the samples produced by staged heating of the starting materials. Crystalline or amorphous Na5 W14 O44 formed during heating partially due to the protection by molten B2 O3 . Subsequently, amorphous Na5 W14 O44 clusters are present in the glass acting as NIR-shielding functional units. This study sheds a light on further development of non-film-based and highly efficiency energy-saving windows.